PENGARUH KUALITAS PELAYANAN, TAMPILAN MUSEUM DAN MANAJEMEN KOLEKSI TERHADAP KEPUASAN WISATAWAN MONUMEN YOGYA KEMBALI - Panghastuti, Tuti (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2016)
Museums are more important than ever before. They play a substantial role in people‟s leisure activities and belong to one of the most importance tourist attractions. The visitors have a strong effect on local economies, especially in touristic locations. Not surprisingly therefore more and more museums are founded usually in spectacular buildings. This research employs three dimention of service quality to understand the factors underlying tourist satisfaction of „Monumen Yogya Kembali‟.These dimentions investigated are namely Service Quality, The Appearance of the Museum and Collection Management. Sampling has been conducted at the Monumen Yogya Kembali between October 12- 25th 2015. Convenient random sampling has been employed to 100 respondent. Through a 4 point Likert-type scale, tourists‟ expectations of a perfect service provider has been compared with the practices Monumen Yogya Kembali to determine if there are any gaps. Service Quality, the Appearance of the Museum, and Collection Management‟ has been analyzed together with its effects on tourist‟ satisfaction through a regression analysis. Linear regression analysis is conducted to test the research model. The regression modelthat explains the satisfaction variable via Service Quality, the Appearance of the Museum, and Collection Management factors is tested. Accordingly, tested regression model is meaningful (F: 34,651, p < 0.001) and independent variables canexplain the 50,5% of change in the satisfaction variable. Closer analysis of the modelparameters suggests Service Quality, the Appearance of the Museum, and Collection Management variables have a significantly positive effect on satisfaction. Keyword : Monumen Yogya Kembali, Service Quality, The Appearance of the Museum, Collection Management, Tourist, Satisfaction.